Optimal conditions for pollen storage of Ochroma pyramidale - Jalca Zambrano, Ivonne; García Cruzatty, Luz Cecilia; Castro Olaya, Jessenia; Villamar Torres, Ronald; Guachambala Cando, Marcelino (BOSQUE, 2019)
Knowledge about pollen biology is fundamental for the planning of controlled crosses in programs of conservation and genetic improvement of plant species. The objectives of this research were to determine the ideal medium for in vitro germination of pollen and to evaluate the effect of temperature and drying on the viability of stored pollen from Ochroma pyramidale. Pollen was obtained from flowers collected before anthesis. The appropriate culture medium for in vitro germination of pollen was determined by testing modifications of the medium proposed by Brewbaker and Kwack. Pollen drying was performed during different times (60, 120, 180 and 240 minutes) at 29 °C and 45 % relative humidity. These samples were stored under temperatures of 5, -20 and -196 °C, and evaluated for 45 days. The ideal medium for pollen germination was composed of 10 % sucrose, 30 mg L-1 boric acid, 430 mg L-1 calcium nitrate. The initial viability calculated by in vitro germination was high, which indicates that the individuals evaluated can be used as pollen donors in the controlled crossing plans. Humidity below 5 % allowed keeping the pollen stored, independently of the storage temperature during the 45 days of the test, without significant decrease in their viability and germination rate. However, pollen viability decreased rapidly when it was stored with high moisture content, regardless of storage temperatures.